Optimization of exopolysaccharide overproduction by Lactobacillus confusus in solid state fermentation under high salinity stress - Seesuriyachan P. (2017)
It is believed that high concentrations of sodium chloride (NaCl) suppress the biosynthesis of exopolysaccharide (EPS) in lactic acid bacteria (LAB). Nevertheless, overproduction of EPSs due to high salinity stress in solid state fermentation performed on an agar surface was demonstrated in this study using a response surface methodology via a central composite design (CCD). Under optimized conditions with NaCl 4.97% and sucrose 136.5 g/L at 40.79 h of incubation, the EPS yield was 259% (86.36 g/L of EPS), higher than the maximum yield produced with the modified MRS medium containing only 120 g/L of sucrose without NaCl (33.4 g/L of EPS). Biosynthesis of EPS by Lactobacillus confusus TISTR 1498 was independent of biomass production. Our results indicated that high salinity stress can enhance EPS production in solid state fermentation.